DISTRIBUSI CEMARAN LOGAM BERAT KROMIUM (Cr) DI SEKITAR INDUSTRI PELAPISAN LOGAM DESA SUSUT, BANGLI - I M., Siaka (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 4 No 2)
An investigation on the distribution of contamination of heavy metals chromium (Cr) in around Industrial Metal Coating at Susut Village, Bangli has been carried out. Allegedly contaminated soil by metal chromium (Cr) was analyzed by means of AAS (Atomic Absorption Spectroscopy) with prior process of digestion method using a mixture of mineral acids, HNO3 and H2O2 (1:1). It was found that, the distribution of heavy metals chromium varied according to the distance (0 – 50 m) between the pollutant sources and the sampling locations. The soils collected from West side of the industry contained Cr ranging from 13.4742 to 24.2507 mg/kg, while the soils collected from the North and South sides of the industry contained Cr of 9.9725 – 19.6718 mg/kg and 19.9415 – 25.8771 mg/kg respectively. Moreover, the distribution of Cr showed a positive correlation between depths (0 – 40 cm) and the Cr concentrations. The deeper was the soils, the higher the concentration of Cr was. The concentration of Cr ranged from 3.5022 to 30.7174 mg/kg and the highest concentration of Cr was distributed in the depth of 40 cm.
Keywords: distribution, pollutant, heavy metals, Cr